Verkehrssicherheit in den Kreisen Nordrhein-Westfalens: Wo lebt es sich am sichersten? - Holz-Rau, Christian; Scheiner, Joachim (Raumforschung und Raumordnung | Spatial Research and Planning, 2010)
The paper presents traffic accident risk figures for North Rhine-Westphalia on the district level (Kreise and kreisfreie Städte), broken down by age group and type of traffic participation. The spatial analysis is based on the victims’ places of residence. These are identified for car passengers by using licence numbers. Injured or killed pedestrians and bicycle users are classified by place of accident, which may serve as a good proxy for the place of residence in their case. The results suggest that the population-based risk to be killed or seriously injured in road traffic is considerably lower in large cities than in suburban and rural areas. This is particularly true for adolescents. Macro-economically, this leads to markedly below-average accident costs in large cities.
Keywords: Traffic safety; Traffic accident; Residential location choice; North rhine-Westphalia